High‐level intrathymic thyrotrophin receptor expression in thyroiditis‐prone mice protects against the spontaneous generation of pathogenic thyrotrophin receptor autoantibodies. (20th February 2017) - McLachlan, S. M.; Aliesky, H. A.; Banuelos, B.; Lesage, S.; Collin, R.; Rapoport, B.
Summary: The thyrotrophin receptor (TSHR) A‐subunit is the autoantigen targeted by pathogenic autoantibodies that cause Graves' hyperthyroidism, a common autoimmune disease in humans. Previously, we reported that pathogenic TSHR antibodies develop spontaneously in thyroiditis‐susceptible non‐obese diabetic (NOD). H2 h4 mice bearing a human TSHR A‐subunit transgene, which is expressed at low levels in both the thyroid and thymus (Lo‐expressor transgene). The present study tested recent evidence that high intrathymic TSHR expression protects against the development of pathogenic TSHR antibodies in humans. By successive back‐crossing, we transferred to the NOD. H2 h4 background a human TSHR A‐subunit transgene expressed at high levels in the thyroid and thymus (Hi‐expressor transgene). In the sixth back‐cross generation (> 98% NOD. H2 h4 genome), only transgenic offspring produced spontaneously immunoglobulin (Ig)G class non‐pathogenic human TSHR A‐subunit antibodies. In contrast, both transgenic and non‐transgenic offspring developed antibodies to thyroglobulin and thyroid peroxidase. However, non‐pathogenic human TSHR antibody levels in Hi‐expressor offspring were lower than in Lo‐expressor transgenic mice. Moreover, pathogenic TSHR antibodies, detected by inhibition of TSH binding to the TSHR, only developed in back‐cross offspring bearing the Lo‐expressor, but not the Hi‐expressor, transgene. High versus low expression human TSHR A‐subunit in the NOD. H2 h4 thymus was not explained by the transgene locations, namely chromosome 2 (127–147 Mb; Hi‐expressor) and chromosome 1 (22.9–39.3 Mb; low expressor). Nevertheless, using thyroiditis‐prone NOD. H2 h4 mice and two transgenic lines, our data support the association from human studies that low intrathymic TSHR expression is associated with susceptibility to developing pathogenic TSHR antibodies, while high intrathymic TSHR expression is protective. Abstract : Pathogenic TSHR antibodies, detected by inhibition of TSH binding to the TSHR, only developed in NOD.H2h4 backcross offspring bearing the Lo‐expressor, but not the Hi‐expressor, human TSHR A‐subunit transgene. These findings in a mouse model are consistent with recent evidence in humans that high intra‐thymic TSHR expression protects against the development of pathogenic TSHR antibodies.